Funkcije ceste u izgrađenom području i mjere smirivanja prometa - Golubić, Jasna (Promet - Traffic&Transportation, 2012)
This paper deals with a major function of the road in populated areas with particular reference to the measures taken on abatement of traffic flows. Considering the fact that major part of the area designed for traffic in populated areas has been used for purposes of road traffic to disadvantage of pedestrians and cyclists, it is necessary to initiate activities on purposes of structuring of the road area and this by measures of abatement of traffic flows with the basic objective of humanization of traffic i.e. harmonization of community life and traffic in the urban area. This paper deals with some examples of listed measures with low, r:cdiwn and high funding requirements.